Socio-economic Status and Infant Mortality Rate: Socio-Economic Status and Infant Mortality Rate - Gholami Taramsari 1, Mahshid; Moeini 1*, Seyed Reza; Kazemipour 2, Shahla (Shahroud Journal of Medical Sciences, 2021)
Backgrounds: For more than forty years medical sociology has explained numerous examples of the social patterning of disease. They have shown a strong association between health and socioeconomic status (SES). One of the most important indicators of development in each country is the infant mortality rate, and SES is main determinant for this indicator. This study has evaluated the impact of SES on infant mortality in Shahroud, 2017.Methods: In This cross-sectional study, the information of 4242 children born in 2017 was extracted from the electronic health record with the help of the Data Collection Form. In the first part, the information was about demographics and health care of the household. The second part was related to the household economic status, it was asked to the mothers by phone or in person, including questions about the equipment and tools used by the household. The PCA method (Principal Component Analysis) was used to determine the socio-economic status, and finally, the households were divided into two high and low socio-economic groups. Confounding factors such as mothers’ gravidity, history of congenital anomalies in previous children, mother age, history of abortion, type of delivery, the interval of pregnancies, were also used in the study to investigate the effect of SES on infant mortality.Results: Based on our findings, out of 4242 children born in 2017, a total of 21 children died before one year old. The chance of death in children of households belonging to the low SES was 2.93 times more than high SES (CI95% = 1.14-7.54).Conclusions: In general, improving households’ socio-economic status can be very effective in reducing child mortality. Government, non-government, and NGO supports can help to improve the economic situation of households and they can help poor families to receive some expensive health services. It is also recommended to promote family health literacy.Keywords: Socio-economic status, Principal component analysis, Infant, Mortality, Shahroud.